The imperceptible scorpion: a short study on the visual and symbolic language of an erotic stamp seal impression found at Tepe Gawra - Paszke , Marcin Z. (Acta Archaeologica Lodziensia, 2023)
This paper examines a group of erotic stamp seal impressions found at Tepe Gawra, chiefly in the context of ancient Mesopotamian glyptic art. The aim of the work is to reinterpret those curious objects found with a representation of a mating couple on a seal, labelled by Tobler as no. 86 with the image of a scorpion. The article focuses on the motif of a scorpion, its morphology, its iconography, its cultural and symbolic meaning. The symbol of a scorpion, deeply immersed in the sphere of fertility and magic, seems to play a key role for the proper understanding of the visual language of the erotic scenes found at Tepe Gawra.